A Geopolitical Analysis on the Issue of the Water Reserves in Middle East. - Ioannis Mazis (Journal of Oriental and African Studies, 1995)
Water reserves represent a vital goal of the Arab-Israeli peace negotiations (A/I/N). The multilateral negotiations, that started in Madrid in November 1991 under the tutelage of USA and Russia and continued in Washington after September 1992 together with the bilateral discussions on regional problems (sovereignty issues and administrative status of the Palestinians), have been followed by seven rounds of discussions on the issue of the water, in which participated Israel, on the one side, and a Palestinian-Israeli delegation, on the other. These seven rounds were held in first place, in Moscow in January 1992, then in Vienna (13-14 May 1992), Geneva (May 1993), Peking (26-28 October 1993), Mascat (17-20 April 1994), Athens (7-9 November 1994) and, finally, in Amman (18-22 June 1995).1 None of these meetings had been successful because Syria and Lebanon were absent. The governments of Syria and Lebanon stated that any discussion of the multiple aspects of the conflict, such as the arms control, the refugee problem, the economic development and the protection of the environment, is without significance as long as Israel continues to occupy Palestinian territory. The above governments, since the Madrid meeting, have already made clear that their first concern is the contrivance of an international legal status that will settle the existing bellicose situation, due to the territories that Israel has occupied and principally the Golan Heights, between them and Israel.